Management and Quality Control of Large Neuroimaging Datasets: Developments From the Barcelonaβeta Brain Research Center - Huguet, Jordi; Falcon, Carles; Fusté, David; Girona, Sergi; Vicente, David; Molinuevo, José Luis; Gispert, Juan Domingo; Operto, Grégory; , for the ALFA Study (Frontiers in Neuroscience, 2021)
Recent decades have witnessed an increasing number of large to very large imaging studies, prominently in the field of neurodegenerative diseases. The datasets collected during these studies form essential resources for the research aiming at new biomarkers. Collecting, hosting, managing, processing or reviewing those datasets is typically achieved through a local neuroinformatics infrastructure. In particular for organizations with their own imaging equipment, setting up such a system is still a hard task, and relying on cloud-based solutions, albeit promising, is not always possible. This paper proposes a practical model guided by core principles including user involvement, lightweight footprint, modularity, reusability and facilitated data sharing. This model is based on the experience from an 8-year old research center managing cohort research programs on Alzheimer’s Disease. Such a model gave rise to an ecosystem of tools aiming at improved quality control through seamless automatic processes combined with a variety of code libraries, command line tools, graphical user interfaces and instant messaging applets. The present ecosystem was shaped around XNAT and is composed of independently-reusable modules which are freely available on GitLab/GitHub. This paradigm is scalable to the general community of researchers working with large neuroimaging datasets.